Language and Spirit
VIII, 153 p.
Keywords: God is said to be Spirit, but the language of spirit is ignored in contemporary philosophy of religion. As well as exploring the notion of spirit in Hegel, Romanticism and Kierkegaard, participants explore the view that God is a spirit without a body, and the relations between 'spirit' and 'truth'.